Using Plant DNA Barcodes and Functional Traits to Assess Community Assembly of Quercus Forests at Different Scales in the Semiarid Loess Plateau of China - YongFu Chai; TingTing Tian; Luyao Wang; Junxin Wei; Yao Xu; Peiliang Liu; Chengcheng Xiang; Ming Yue (Ecology and Evolution)
ABSTRACT Trait and evolutionary differences among coexisting species are increasingly used to comprehend the processes shaping communities. However, they do not consistently yield congruent insights due to methodological limitations and scale dependence. Utilizing two plastid DNA genes (rbcL and matK) and one nuclear DNA gene (internal transcribed spacer, ITS), we first constructed the phylogenies of 147 woody species from 98 line transects in the forest areas of the Loess Plateau and subsequently measured three functional traits. Five plots (2500 m2) were constructed within Quercus forests to analyze the functional and phylogenetic structures at three spatial scales (100, 400, 2500 m2) and two vertical structural layers (tree colonization and shrub layer). In contrast to the phylogenetic convergence observed at the genus level, using plant DNA barcodes, we found that the entire forest communities and the tree layer exhibited phylogenetic randomness across all three spatial scales; even the shrub layer showed phylogenetic overdispersion with increasing scale. Specific leaf area (SLA) exhibited functional convergence in both the shrub and tree layers. In contrast, seed mass (SM) and plant height (PH) displayed distinct functional structures. In the tree layer, these traits showed phylogenetic overdispersion, while in the shrub layer, they demonstrated functional convergence. This contrast highlights the different ecological roles and processes at play in the two layers. Specifically, the scale dependency of assembly patterns in the shrub layer was more pronounced than in the tree layer for both functional and phylogenetic structures. Our findings underscore the significance of employing DNA barcodes to assess the phylogenetic structure of communities with closely related coexisting species and emphasize niche‐based functional assembly and multi‐process phylogenetic assembly among vertical structural layers in the Quercus community. Decoupling functional and phylogenetic disparities between species could facilitate the understanding of complex species differences influencing community assembly.